تأثير استخدام طريقة السماع و المحافظة على استيعاب المفردات في الفصلالسابع المتوسطة بالمدرسة الإسلامية أولو النهى ميدان جوهور - Tambunan, Isna Aprila; Manik, Wagiman; Ulum, Bahrul (ANWARUL, 2024)
The formulation of the problem in this research is, (1) what is the ability of first grade students at Ulun Nuha Islamic Middle School in Medan to master mufrodath using imitation and memorization methods, (2) what is the ability of first grade students at Ulun Nuha Islamic Middle School in Medan to master mufrodath without using the method imitating and memorizing, (3) what is the influence of the use of imitating and memorizing methods on the mastery of mufrodath in the first grade of Ulun Nuha Islamic Middle School, Medan. The research method used is quantitative research in the form of an experimental research method and data analysis techniques using statistics with a True Experimental research design with a posttest-only control design. And the female students' scores have been obtained: (1) By using the method of imitating and memorizing the mastery of mufrodath in the experimental class using the formula with the achievement "Jayyid" with an average score of 79.9, (2) Meanwhile the level of ability of female students without using the method of imitating and memorizing mastery of mufrodath in the control class using a formula with the achievement "Jayyid Murtafi'" with an average score of 51.8, (3) Then there is the influence of using imitation and memorization methods on mastery of mufrodath by referring to the value of the t-test using the formula, namely the value t0 is greater than the tt value, 9.52 > 2.76. And this explanation shows that the alternative hypothesis is accepted. So it can be concluded that there is an influence of the use of imitation and memorization methods on mastery of mufrodat.